An EMG preprocessing pipeline and a GUI for paralympic cross-country skiing sitting position assessment - Barioudi, H.; Hirsch, L.; Wintergerst, D.; Rombach, R.; Rapp, W.; Felderhoff, T.; Mrachacz-Kersting, N. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
An efficient sitting position and the sledge design are crucial for the success of para-athletes in cross-country sit skiing. However, there is a lack of studies on the effects of sitting positions on the performance of para-athletes. This study introduces an EMG preprocessing pipeline and a GUI to analyse and compare muscle activation in different sitting positions, as well as identify key factors to quantify the optimal sitting position. As desired by the coaches, this provides the opportunity to compare muscle activation during different sitting positions and conditions immediately after measurements. Test measurements were conducted with non-disabled athletes to validate the functionality of the EMG preprocessing pipeline and the developed GUI. This could allow coaches to quickly gain insights into the specific requirements of each athlete and make informed decisions on how the sitting position should be adjusted to improve performance and prevent injuries.